EVALUASI KESESUAIAN LAHAN UNTUK PERMUKIMAN DI KANAGARIAN PAINAN KECAMATAN IV JURAI KABUPATEN PESISIR SELATAN - Veni Veni (STKIP Pesisir Selatan, 2016)
This research aims to evaluate the characteristics of land for settlements and to evaluate the land suitability classes. This is a descriptive research. The samples take by land units with a sampling technique is stratified random rampling. The methode used in this research were survey, laboratorium test, scoring on each characteristics of land so as to obtain the level of suitability of land for settlements and overlay. The research result showed that in Kanagarian Painan there are three landforms, namely fluvialandform, volcanic landform and marine landform. Based on the result of the analysis of characteristis of the land suitability (drainage, permeability, slope, duration of inudation, soil teksture, distribution fo coarse material, host rock outcrop, depth expanse of rock, depth of groundwater) there are three classes of suitability land for settlements in Kanagarian Painan are land suitable for settlements (11 ha), enoughland suitable for settlement(349 ha) and land less suitable for settlement(8 ha).